Hubungan Kecemasan dengan Perubahan Degeneratif Fisik Wanita Premenopause di Kelurahan Biringgere Kab. Sinjai - Ramli, Kamrianti; Khairiyyah, Khairiyyah; Suharni, Suharni (JURNAL KESEHATAN REPRODUKSI, 2017)
Background : Premenopausal afflicts woman of 40 years old and above. Premenopausal symptoms is characterized by declining estrogen levels causing psychological disorders such as anxiety.Objective : The aim of this study was to analyze the relationship of anxiety and physical degenerative changes of women in 40-45 years old in Biringgere district, Sinjai regency.Method: This research used analytic descriptive survey with cross sectional approach. The population in this study were premenopausal women in age 40-45 years, while the samples in the study were premenopausal women married in 40-45 years old who have inclusion and exclusion criteria as many as 86 respondents. The sampling technique was purposive sampling technique. The instrument used in this study is questionnaire. The data analysis was univariate and bivariate analysis where the statistical test was the chi-square test.Result and Discussion: This result was relevant with statistic test result obtained that significant level of p = 0.000 <0.05. It means that there was a very strong relationship between anxiety with physical degenerative changes in premenopausal women in Biringgere district, Sinjai regencyConclusion: physical degenerative changes affect the occurrence of anxiety premenopausal women.Keywords: premenopausal women, anxiety, physical degenerative changes.